Antibacterial resistance: a comparative study between clinical and environmental isolates - Mosharraf, Fahareen Binta; Anindita, Monisha; Kalam, Iftekhar Mohammad Shafiqul; Karim, Mehnaz (© 2016 Published by BRAC University, 2017)
This article was published in the BRAC University Journal [© 2016 Published by BRAC University].